From Population Age Structure and Savings Rate to Economic Growth: Evidence from Ecuador - Rosado, Joel Alejandro; Alvarado Sánchez, MarÃa Isabel (International Journal of Economics and Financial Issues, 2017)
This paper studied the relationship between the dependency ratio, savings rate and real GDP for Ecuador for the period 1975–2015. Starting with the unit root tests given the use of time series and the cointegration results, the dynamic ordinary least squares (DOLS) and fully modified ordinary least squares (FMOLS) were used to show the relationship between the variables in the long-run. In the short-run, vector error correction model (VECM) was applied to estimate the relationship. In several degrees, the long-run relationship between the dependency ratio, savings rate and real GDP was proved; Granger causality tests show a one-way causality running from the savings rate to GDP per capita. The interaction between the variables in the post-sample period is also forecast using impulse response functions (IRFs) and variance decomposition (VDC) analysis. The overall result implies that changes in population age structure had a significant impact on real GDP per capita in Ecuador. However, this advantage of the age structure may disappear soon due to the projected rapid increase in the dependency ratio because of ageing of the population which may lead to a slowdown in the GDP growth. Keywords: Cointegration, Dependency ratio, Gross domestic product, Impulse response functions, Savings rate, Structural breaks, Variance decomposition JEL Classifications: J11, J14, O11